Critical innovations in the UK peer-to-peer (P2P) and equity alternative finance markets for small firm growth. (August 2016) - Culkin, Nigel; Murzacheva, Ekaterina; Davis, Andrew
This paper examines the disruptive nature of financial innovations available to small firms by the growing range of online platforms that have emerged in the United Kingdom since the financial crisis. It is unveiled that finance provided to small firms via such mechanisms is not identical to more traditional sources, and its adoption therefore cannot be said to be simply a question of direct substitution based, for example on a price comparison. These offer a series of important advantages over more traditional sources of early-stage capital for entrepreneurs seeking funding. Service innovations around security, flexibility of terms, speed of access and transparency of pricing are as important as price considerations for many users, as are innovations made possible by the way, these online markets are structured and in particular in the way these innovative structures allow important types of risk to be dispersed and mitigated.